Течения: история взросления и обретения себя : роман / Даша Благова - Благова Даша (Альпина. Проза, 2024)
Экземпляры: ЦБ/14/32 (20250403) / Инвентарный номер: 67876 / Цена: 529.00 / Сис.шифр: Р2 / Авт.знак: Б 68 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6